A Study on the Estimation of Fees for Dental Hygiene Activities Within the Dental Hygiene Process Using the Relative Value Scale - Jin-Sun Choi; Sun-Jung Shin; Bo-Mi Shin; Hyo-Jin Lee; Hye-Young Yoon; Soo-Myoung Bae (치위생과학회지)
Background: Dental hygienists serve as preventive care providers, oral health educators, and public health advocates. Although the dental hygiene process (DHP)—a patient-centered, evidence-based model—is widely used in dental hygiene education, its clinical application in Korea is limited due to legal constraints and lack of institutional recognition. Current fee structures do not reflect the complexity, workload, or time required for specific dental hygiene tasks. This study aimed to classify dental hygiene activities by DHP phase and estimate procedure-specific fees using task intensity, relative value units (RVUs), and procedural time as a basis for proposing a value-based reimbursement model. Methods: Activities were extracted and categorized according to the four phases of the DHP—assessment/diagnosis, planning, implementation, and evaluation—using the Standard Clinical Dental Hygiene Guidelines and the Research on the identification of dental hygiene activities for determination of fees for dental hygiene activities (2021). RVUs were assigned to each activity, and fees were calculated using conversion factors published by the National Health Insurance Service for 2024 (₩96.3) and 2025 (₩99.1). Results: Results showed that the implementation phase had the highest average RVUs and projected fees, particularly for procedures like scaling and root planing. While the assessment/diagnosis phase had lower average RVUs, several activities within it demonstrated high workload and clinical importance. Planning and evaluation activities also showed substantial time and value, including treatment plan explanation and professional collaboration. Conclusion: This study provides empirical evidence supporting a structured, workload-based reimbursement system for dental hygienists. By aligning RVUs with clinical realities, these findings lay a foundation for integrating dental hygiene procedures into national health insurance policies and strengthening the profession’s identity and value.